2012
DOI: 10.1038/onc.2012.300
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic-induced repression of microRNA-205 is associated with MED1 activation and a poorer prognosis in localized prostate cancer

Abstract: Deregulation of microRNA (miRNA) expression can have a critical role in carcinogenesis. Here we show in prostate cancer that miRNA-205 (miR-205) transcription is commonly repressed and the MIR-205 locus is hypermethylated. LOC642587, the MIR-205 host gene of unknown function, is also concordantly inactivated. We show that miR-205 targets mediator 1 (MED1, also called TRAP220 and PPARBP) for transcriptional silencing in normal prostate cells, leading to reduction in MED1 mRNA levels, and in total and active pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 53 publications
4
64
0
Order By: Relevance
“…Active H3K4me3 and repressive H3K27me3 not erased during development could also affect nucleosomes in mature sperm and possibly induce divergences in the insertion of histone variants during repackaging of the haploid genome. Cross-talk between DNAme and histone PTMs also exists and theses epigenetic marks can regulate the expression and the stability of ncRNAs in somatic cells (Hulf et al 2013 ;Das et al 2013 ). Interactions between epigenetic marks and ncRNAs might occur during different stages of spermatogenesis.…”
Section: Inductionmentioning
confidence: 98%
“…Active H3K4me3 and repressive H3K27me3 not erased during development could also affect nucleosomes in mature sperm and possibly induce divergences in the insertion of histone variants during repackaging of the haploid genome. Cross-talk between DNAme and histone PTMs also exists and theses epigenetic marks can regulate the expression and the stability of ncRNAs in somatic cells (Hulf et al 2013 ;Das et al 2013 ). Interactions between epigenetic marks and ncRNAs might occur during different stages of spermatogenesis.…”
Section: Inductionmentioning
confidence: 98%
“…miR-205 is possibly the best-characterized tumor suppressor miRNA in prostate cancer. Hypermethylation of the MIR-205 locus is associated with a decrease in miR-205 expression in prostate cancer cell line LNCaP (40-fold induction upon 5-Aza-CdR treatment) and localized prostate cancer compared with matched histologically benign prostate tissue (24). MIR-205 hypermethylation was also shown to be a significant predictor of biochemical recurrence (24).…”
Section: Micrornasmentioning
confidence: 99%
“…Hypermethylation of the MIR-205 locus is associated with a decrease in miR-205 expression in prostate cancer cell line LNCaP (40-fold induction upon 5-Aza-CdR treatment) and localized prostate cancer compared with matched histologically benign prostate tissue (24). MIR-205 hypermethylation was also shown to be a significant predictor of biochemical recurrence (24). Argonaute-2 co-immunoprecipitation experiments revealed that miR-205 targets mRNAs involved in mitogen-activated protein kinase and androgen receptor signaling pathways, including the AR itself (25,26).…”
Section: Micrornasmentioning
confidence: 99%
“…On the other hand, DNA methylation is a key mechanism to regulate gene expression, and many important genes are silenced by DNA methylation in PC, such as AR, 18 GSTP1, 19 CD44, 20 microRNA-375, 21 and microRNA-205. 22 The aim of the present study was to determine whether DNA methylation is involved in the expression of TMPRSS2 and what molecule regulates the DNA methylation of TMPRSS2. Our study provides evidence that high level of DNA methyltransferases 1 (DNMT1) appears to be the mechanism for the hypermethylation-mediated transcriptional repression of TMPRSS2 in AR-negative PCa cells.…”
Section: Introductionmentioning
confidence: 99%